Visualisasi Data Penjualan dan Produksi PT Nitto Alam Indonesia Periode 2014-2018 - Dessy Aryanti; Johan Setiawan (Universitas Multimedia Nusantara, 2018)
PT Nitto Alam Indonesia is a Manufacturing company engaged in screw manufacturing services. The company has a total of 134,252 rows sales and production data, but the data has never been analyzed so that the information is still not fully explored. This research proposes to make a visualization in the form of a dashboard containing sales and production data at PT Nitto Alam Indonesia in 2014 – 2018. It will be shown by using visual data mining (VDM) method with Tableau Software tools. The purpose of this study was to assist PT Nitto Alam Indonesia in analyzing sales and production data to find information that had never been explored before. The results of this study are that the patterns of sales and production can be known for the last 5 years. The sales pattern is included in the type of cycle with the highest sales peak located in the fourth quarter in 2017 at 6.552%. In addition, the performance of sales and production from 2014 to 2018 increased consistently. This research has been validated by applying User Acceptance Tests at PT Nitto Alam Indonesia.